Single-cell RNAseq reveals adverse metabolic transcriptional program in intrahepatic cholangiocarcinoma malignant cells - Christophe Desterke; Raquel Francés; Claudia Monge; Yuanji Fu; Agnès Marchio; Pascal Pineau; Jorge Mata-Garrido (Biochemistry and Biophysics Reports)
Intrahepatic cholangiocarcinoma (ICA) is a highly aggressive primary liver cancer, which originates from the epithelial cells of the bile ducts. The transcriptional profile of metabolic enzymes was investigated at both bulk and single-cell levels in tumor samples from distinct ICA cohorts. In a training cohort (TCGA consortium), 16 genes encoding for metabolic enzymes were found overexpressed in cases with poor survival. A computed metabolic gene expression score was significantly associated with worse ICA prognosis at the univariate level (overall survival [OS] log-rank p = 8.2e-4). After adjusting for Ishak fibrosis score and tumor staging, the metabolic expression remained an independent predictor of poor prognosis (multivariate OS log-rank p = 0.01). Seven genes encoding key enzymes (FH, MAT2B, PLOD2, PLOD1, PDE6D, ALDOC, and NT5DC3) were validated as markers of the proliferative subclass of ICA in the GSE32225 dataset, related to poor prognosis. The metabolic score was significantly different between the inflammatory and proliferative subclasses in the validation cohort (p < 2.2e-16). At the single-cell level, in the tumor microenvironment of 10 ICA patients, these seven enzymes were predominantly expressed by malignant cells. The single-cell metabolic score was thus higher in malignant cells. This study identifies a metabolic transcriptional program linked to poor prognosis in ICA, independent of fibrosis and tumor staging.